Ensemble, on va plus loin ? Différences d’appréciation du travail à plusieurs chez des élèves de primaire - Amélia Legavre (Éducation et Socialisation)
This article focuses on the appreciation of collective work from pupils of three classes of primary schools, based on the observation of these classes and on the interviews of the 67 pupils of these classes. The article questions the role of interactions for the subjective experience of the students, from their own point of view: do the students appreciate the collective work and if so, do they appreciate it for the same reasons? First of all, the results show that collective work is very much appreciated by the pupils, but that the pupils with a high academic level value several modalities of it, whereas the pupils with a lower level value what’s opposed the most from formalized exercises. A second part focuses on the experience of insecure students, who find in collective work a source of comfort, which protects them from unpleasant situations, in terms of facing their academic or relational difficulties. Finally, pupils with a high academic level and rather sure of their status within the class find some interest in interactions in terms of intellectual added value. Thus, it is possible to conclude that collective work improve the experience of students from their point of view, but for different reasons depending on their profiles.